The Role of Ants in Lowland Tropical Rainforest Transformation - Noor Farikhah Haneda; Nisfi Yuniar (Jurnal Ilmu Kehutanan)
Deforestation or changes functions from forest to non-forest play a role in changing ecosystems and the species within them. Insect as one of the fauna is an interesting aspect to study, especially ants. Aims of this study is to identify the roles of the genus of ants that found in the transformation ecosystem. This study was conducted in Bungku Village, Bajubang District, Batanghari Regency, Jambi. Method used in this study is to make a plot of observation by purposive sampling. Ant sampling techniques use pitfall traps in four ecosystems i.e.. secondary forest, oil palm plantation,rubber plantation, and jungle rubber. This study found 33 genera from 6 subfamilies. Furthermore, 33 genera are grouped based on their roles, i.e. (1) 46% foragers, (2) 36% for predators, (3) 3% for army ants, (4) 3% for scavengers, and (5) 3% for others (harvesting ants, omnivores, predators and scavengers too). Camponotus as the dominant genus has a role for foragers, and Pheidole has a role as a seed destroyer and the other part is omnivorous.